Cerebral dominance - evaluation of the methods of its determination and its clinical uses - Rama Mohan Babu P; Swarnalatha KC (Journal of All India Institute of Speech and Hearing, 1972)
In this paper the concept of cerebral dominance for various functions withemphasis on speech, is examined in the light of the recent literature available to us.A few ways in which this knowledge of cerebral dominance can be used in thedifferential diagnosis of speech disorders due to cortical lesions have been discussed.And, finally, some of the methods which help in determining the "dominanthemisphere" are pointed out